1993
DOI: 10.4319/lo.1993.38.3.0613
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peritrich ciliates on the production of Acartia hudsonica in Long Island Sound

Abstract: We studied the effects of attached peritrich ciliates on the fitness of natural populations of Acartia hudsonica (Pinhey) in Stony Brook Harbor, Long Island Sound. Ciliate infection occurred during late spring, and ciliate load (No. ind.-') was not related to copepod age, stage, or body size. Simulated in situ experiments conducted throughout the period of abundance of A. hudsonica showed that egg production rate (No. d-l) was positively correlated to ambient water temperature, but negatively correlated to ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…This was not the case for the ciliate Rhabdostyla sp. which was more abundant on adult Acartia hudsonica than on the copepodites (Weissman et al 1993). Likewise, the ciliate Vorticelia microstoma exhibited higher infestation rates on longer Scapholeberis kingi, which was attributed to the fact that younger individuals grew and molted at a faster rate than older individuals (Henebry and Ridgeway 1979).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This was not the case for the ciliate Rhabdostyla sp. which was more abundant on adult Acartia hudsonica than on the copepodites (Weissman et al 1993). Likewise, the ciliate Vorticelia microstoma exhibited higher infestation rates on longer Scapholeberis kingi, which was attributed to the fact that younger individuals grew and molted at a faster rate than older individuals (Henebry and Ridgeway 1979).…”
Section: Discussionmentioning
confidence: 82%
“…Herman and Mihursky (1964) reported that Acartia tonsa carried 25-200 Zoothaminium sp., and Weissman (1993) reported that Acartia hudsonica adults carried 1-300 Rhabdostyla sp., while copepodites and nauplii carried 1-100 ciliates per individual.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antifouling mechanisms should be beneficial if they reduce otherwise adverse effects by fouling organisms, e.g. increased energy expense for locomotion, damage of the body surface with increasing risk of infections, lower egg production, disruption of the moulting cycle (Glynn, 1970;Turner et al, 1979;Nagasawa, 1987;Xu & Burns, 1991;Weissmann et al, 1993).…”
Section: Introductionmentioning
confidence: 99%